2022
DOI: 10.3390/rs14184441
|View full text |Cite
|
Sign up to set email alerts
|

A CNN-LSTM Model for Soil Organic Carbon Content Prediction with Long Time Series of MODIS-Based Phenological Variables

Abstract: The spatial distribution of soil organic carbon (SOC) serves as critical geographic information for assessing ecosystem services, climate change mitigation, and optimal agriculture management. Digital mapping of SOC is challenging due to the complex relationships between the soil and its environment. Except for the well-known terrain and climate environmental covariates, vegetation that interacts with soils influences SOC significantly over long periods. Although several remote-sensing-based vegetation indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The MPM model consists of two different parallel networks, CNN and LSTM (the framework is shown in Figure 2). (1) Data collection and preprocessing: abnormal data were eliminated, and data format conventions and normalization were carried out for environmental variables and target values (Yang D. S. et al, 2020) (3) Feature fusion layer: There are two main feature fusion methods in hybrid neural networks: addition (Yang J et al, 2020) and concatenation (Zhang et al, 2022). Feature addition requires the same dimension of feature vectors, while concatenation is more flexible.…”
Section: The Framework Of the Mpm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPM model consists of two different parallel networks, CNN and LSTM (the framework is shown in Figure 2). (1) Data collection and preprocessing: abnormal data were eliminated, and data format conventions and normalization were carried out for environmental variables and target values (Yang D. S. et al, 2020) (3) Feature fusion layer: There are two main feature fusion methods in hybrid neural networks: addition (Yang J et al, 2020) and concatenation (Zhang et al, 2022). Feature addition requires the same dimension of feature vectors, while concatenation is more flexible.…”
Section: The Framework Of the Mpm Modelmentioning
confidence: 99%
“…Feature addition requires the same dimension of feature vectors, while concatenation is more flexible. Moreover, feature fusion through concatenation has the effect of reinforcing and interconnecting features (Zhang et al, 2017;Zhang et al, 2022). Therefore, concatenation is used to fuse feature vectors in MPM.…”
Section: The Framework Of the Mpm Modelmentioning
confidence: 99%
“…An LSTM layer exists in the LSTM neural network. The surrounding neurons in the same layer are also affected along with the output layer [43,51].…”
Section: Long Short-term Memory (Lstm)mentioning
confidence: 99%
“…LSTM (Long Short-Term Memory) is a type of recurrent neural network (RNN) designed explicitly for processing sequential data, such as time series. LSTM has been shown to be very effective in univariate time series forecasting and, in many cases, outperforms traditional statistical methods such as ARIMA and exponential smoothing [43,[49][50][51].…”
Section: Lstm In Univariate Time Series Forecastingmentioning
confidence: 99%
“…Analytical techniques have been used to assess the importance of predictor variables, with mathematical methods (e.g., correlation analysis, recursive feature elimination) being the most commonly used (Wadoux et al, 2020). Although statistically important variables are efficient for model calibration, recent studies have suggested that retaining predictor variables with physical meaning would make predictive models more interpretable and improve prediction accuracy (Yang et al, 2021; Zhang et al, 2022). For example, Yang et al (2020) selected remote sensing‐based phenological parameters that were physically related to SOC dynamics in croplands, and they showed that models with phenological parameters exhibited higher accuracy than models with variables lacking physical meaning for predicting topsoil organic C content (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%